Veld restoration strategies in South African semi-arid rangelands. Are there any successes?—A review - Mudau, Humbelani Silas; Msiza, Ntokozo Happy; Sipango, Nkosomzi; Ravhuhali, Khuliso Emmanuel; Mokoboki, Hilda Kwena; Moyo, Bethwell (Frontiers in Environmental Science, 2022)
Rangeland deterioration is a major challenge faced especially by communal farmers in most of the developing countries including South Africa. The high population of people and livestock exert pressure on the rangeland leading to deterioration which results to economic loss, due to a reduction in agricultural activities such as livestock production. The rehabilitation of degraded lands has substantial returns from an environmental, economic and social perspective. Except for the powerful economic justification, initiation of restoration and rehabilitation of lands is still required to address the continuing land degradation across the world. To gain an insight on the impact of rangeland degradation, the basic restoration strategies need to be assessed and implemented. In this review, we have highlighted an overview of rangeland degradation in South Africa; Livestock dependency in rangelands; causes and consequences of rangeland degradation which include the economic impact of rangeland degradation; and rehabilitation strategies. Soil, climate, grazing management are some of the major factors to consider when adopting the veld restoration strategies. In South Africa, all restoration methods can be practiced depending on the area and the nature of degradation. Moreover, past land use system records and rehabilitation resources such as material and skilled labour can be required to have a successful rangeland rehabilitation.